The Oxford Handbook of Personality and Psychopathology Assessment 2022
DOI: 10.1093/oxfordhb/9780190092689.013.14
|View full text |Cite
|
Sign up to set email alerts
|

Personality Assessment Inventory

Abstract: The Personality Assessment Inventory (PAI) is a multiscale, standardized self-administered questionnaire designed to provide a comprehensive assessment of client personality and psychopathology. The measure demonstrates widespread use in clinical, research, and training settings, with practical applications across several assessment specialties, including forensics, neuropsychology, health, and personnel selection. This chapter provides an overview of the theory and development of the PAI, summarizes the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 1 publication
2
38
1
Order By: Relevance
“…However, participants in the current study scored significantly lower on the DERS than those from Wilks et al (2016), t (178.5) = −2.13, p = .03, 95% CI [−13.38, −.52], d = −.32. Participants in the current study were, on average, elevated on the PAI-BOR, M = 43.38, SD = 12.05, with 70.1% scoring above Morey’s (1991) threshold score indicating the likely presence of BPD. Finally, our primary measures of interest were relatively highly correlated at baseline, with r s ranging from |.43| to |.68| (see Table 2).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, participants in the current study scored significantly lower on the DERS than those from Wilks et al (2016), t (178.5) = −2.13, p = .03, 95% CI [−13.38, −.52], d = −.32. Participants in the current study were, on average, elevated on the PAI-BOR, M = 43.38, SD = 12.05, with 70.1% scoring above Morey’s (1991) threshold score indicating the likely presence of BPD. Finally, our primary measures of interest were relatively highly correlated at baseline, with r s ranging from |.43| to |.68| (see Table 2).…”
Section: Resultsmentioning
confidence: 64%
“…The Personality Assessment Inventory-Borderline Features Scale (PAI-BOR; Morey, 1991) is a 24-item self-report questionnaire that assesses specific features of BPD, such as mood instability, anger, impulsivity, and relationship difficulties. The PAI-BOR has been shown to have good internal consistency (baseline α in current sample = .86) and high sensitivity (88.0%) and specificity (88.4%) for individuals meeting criteria for BPD (Southward & Cheavens, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…While up-to-date estimates of prevalence rates are not available for Norway, research in the field places the prevalence as high as 30%, with averages of around 15% (Greve et al, 2009; McDermott et al, 2013; Rumschik & Appel, 2019; Young, 2015). Clinicians will have to resort to the Minnesota Multiphasic Personality Inventory-2 (Ben-Porath & Archer, 2011; Hathaway & McKinley, 1983) or the Personality Assessment Inventory (Morey, 1991) with its well-validated indexes of symptom overreporting (Rogers, 2018b; Rogers et al, 2003) for more comprehensive evaluations of feigning. More targeted and briefer instruments than the Minnesota Multiphasic Personality Inventory-2 or Personality Assessment Inventory would be preferable in many cases, also to be able to combine instruments to increase validity (Giromini et al, 2022).…”
mentioning
confidence: 99%
“…A value >.50 indicates a probability of >50% of overreporting. The original study reported results indicating that the IoP-29 was on par with or better than standard indices in the Minnesota Multiphasic Personality Inventory-2 and the Personality Assessment Inventory (Morey, 1991, 2003).…”
mentioning
confidence: 99%
“…Undergraduate participants were recruited from a psychology subject pool at a Mid-Southern university. Because the main purpose of the study was to examine variability in emotion beliefs over time based on borderline personality pathology (Veilleux, Warner, et al, 2021), potential participants completed a pre-screening measure which included the Personality Assessment Inventory-Borderline Features Scale (PAI-BOR; Morey, 1991), a 24-item index of borderline personality symptoms. People with either high ( T ≥ 70; Raw score ≥ 38) or low ( T < 60; Raw < 18) scores were invited to sign up for the study, where approximately half of the slots were available for high and half for low BPD-features participants.…”
Section: Methodsmentioning
confidence: 99%